2011
DOI: 10.1007/s10120-011-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective palliation and quality of life outcomes in studies of surgery for advanced, non-curative gastric cancer: a systematic review

Abstract: Background Relief of symptoms should be the primary focus of palliative treatment as defined by the World Health Organization. Evaluating the effectiveness of palliative interventions should incorporate this goal and include quality of life (QOL) outcome assessments. A systematic review of the surgical gastric cancer literature was performed to summarize the effectiveness of palliative surgical interventions in addressing QOL. Methods An electronic literature search of EMBASE, Medline, and the Cochrane Databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
0
18
0
2
Order By: Relevance
“…An accurate assessment of health‐related QoL using validated QoL measures is essential to inform clinical decision‐making. Unfortunately, there are few prospective studies using established QoL instruments to assess the impact of surgical palliation in patients with incurable advanced gastric cancer10, even though patient‐reported outcome measures are becoming increasingly important in an effort to give patients a better understanding of the treatment and care options available and outcomes, thereby facilitating decision‐making regarding care26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An accurate assessment of health‐related QoL using validated QoL measures is essential to inform clinical decision‐making. Unfortunately, there are few prospective studies using established QoL instruments to assess the impact of surgical palliation in patients with incurable advanced gastric cancer10, even though patient‐reported outcome measures are becoming increasingly important in an effort to give patients a better understanding of the treatment and care options available and outcomes, thereby facilitating decision‐making regarding care26.…”
Section: Discussionmentioning
confidence: 99%
“…Although some data exist on QoL associated with palliative chemotherapy for advanced gastric cancer6, 7, 8, QoL data associated with surgical palliation are sparse9 10. The aim of this study was to examine the impact of surgical palliation on postoperative QoL in patients with malignant gastric outlet obstruction caused by incurable advanced gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Few of these studies reported information on changes in quality of life or symptom relief, which are the most appropriate primary outcomes in these patients. A detailed summary of quality of life and surgical palliation for surgically managed, advanced gastric cancer patients is reported elsewhere [78]. Procedure-related morbidity, mortality and long-term survival were more variable for patients in whom gastrectomy was not clearly performed for palliation of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Comparando la sobrevida de los 4 grupos de pacientes llama la atención que: a) se aprecia mayor pero no significativa sobrevida en pacientes con metástasis hepáticas solamente, comparados con los otros grupos y b) una mejor sobrevida en pacientes sometidos a gastrectomía total o subtotal que fue significativa. Este hecho ha sido publicado por varios autores extranjeros [14][15][16][17][18][19][20][21][22][23][24][25][26] . Se ha sugerido que el agregado de quimioterapia postoperatoria en pacientes con resección paliativa parece estar asociada a una mayor sobrevida que con la cirugía sola 19,22,23 .…”
Section: Discussionunclassified